When labor enforcement and immigration enforcement collide: Deterring worker complaints worsens workplace safety - Amanda Melina Grittner; Matthew S. Johnson (W.E. Upjohn Institute for Employment Research, 2021)
Regulatory agencies overseeing the labor market often rely on worker complaints to direct their enforcement. However, if workers face differential barriers to complain, this system could result in ineffective targeting and create disparities in working conditions. To investigate these implications, we examine how the onset of Secure Communities - a localized immigration enforcement program - affected occupational safety and health. Counties' participation in Secure Communities substantially reduced complaints to government safety regulators, but increased injuries, at workplaces with Hispanic workers. We show that these effects are most consistent with employers reducing safety inputs in response to workers' decreased willingness to complain.
Keywords: J28; J81; I18; 330; labor regulations; workplace safety; immigration enforcement